(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
The basis of the historiography of the Jadidist movement in Bukhara Emirate was established by its active participant and leader, Sadriddin Aini. His historicalmemoiristic book "Tarikhi irvolutani Bukhara" ("History of the Bukhara Revolution") can rightfully be called the most valuable source and the first study on the history of Bukhara modernism. This book was written in 1918-1919. in the Tajik language, then at the request of the Minister of Education of the BNSR K. Yu. Polatov in 1920-1921